IFFCO Kisan Sancharr Limited ICT Centric Initiative for Empowering Farmers - Malhotra, S (Indian Farming, 2017)
The mobile phone centric approach developed by IFFCO Kisan provides the convenience and comfort of receiving information without having to wait for trickling down of information or depend on doubtful sources for advice. Flexibility of listening to the content at any time and place is a major strength of the approach. Mobile phone not only transcends literacy barrier but provides personal touch to the services. The approach provides Privacy and ‘Any Time’ and ‘Any Place’ access facility of the advisories of the day. IFFCO through ‘IFFCO Kisan’ is ever committed to leverage the latest in ICT to improve the quality of living in the villages. Since its inception, IFFCO Kisan has received several awards and recognitions. The vision of IFFCO in promoting IFFCO Kisan as an institution for promoting rural empowerment received international recognition with the President of the U.S.A., Mr. Barack Obama visiting the Agriculture Expo at St.Xavier’s College in Mumbai on Nov 7, 2010. He was appreciative of the initiative and not only took keen interest in knowing the details but had referred to this in his subsequent speech to the Indian Parliament.